Rhizosecretion improves the production of Cyanovirin‐N in Nicotiana tabacum through simplified downstream processing. Issue 7 (9th March 2016) - Madeira, Luisa M.; Szeto, Tim H.; Ma, Julian K‐C.; Drake, Pascal M.W.
Abstract: Rhizosecretion has many advantages for the production of recombinant pharmaceuticals, notably facile downstream processing from hydroponic medium. The aim of this study was to increase yields of the HIV microbicide candidate, Cyanovirin‐N (CV‐N), obtained using this production platform and to develop a simplified methodology for its downstream processing from hydroponic medium. Placing hydroponic cultures on an orbital shaker more than doubled the concentration of CV‐N in the hydroponic medium compared to plants which remained stationary, reaching a maximum of approximately 20μg/ml in one week, which is more than 3 times higher than previously reported yields. The protein composition of the hydroponic medium, the rhizosecretome, was characterised in plants cultured with or without the plant growth regulator alpha‐napthaleneacetic acid by LC‐ESI‐MS/MS, and CV‐N was the most abundant protein. The issue of large volumes in the rhizosecretion system was addressed by using ion exchange chromatography to concentrate CV‐N and partially remove impurities. The semi‐purified CV‐N was demonstrated to bind to HIV gp120 in an ELISA and to neutralise HIVBa‐L with an IC50 of 6nM in a cell‐based assay. Rhizosecretion is therefore a practicable and inexpensive method for the production of functional CV‐N. Abstract : Cyanovirin‐N (CV‐N) is a lectin which has potential as an HIV microbicide candidate. CV‐N produced by transgenic plants can be secreted out of the roots into hydroponic medium. The authors demonstrate that the yield of CV‐N in the medium is increased by shaking the containers in which plants are cultured. They identify the proteins present in the hydroponic medium (the 'rhizosecretome') and demonstrate that a simple, inexpensive, ion exchange chromatography protocol can produce semi‐purified CV‐N from the medium, which is able to neutralise HIV.